Combined computed tomography-measured tumor density and RECIST for evaluating neoadjuvant therapy in locally advanced gastrointestinal stromal tumors - Su, Wei-Chih; Tsai, Hsiang-Lin; Yeh, Yung-Sung; Huang, Ching-Wen; Ma, Cheng-Jen; Chen, Chau-Yun; Chang, Tsung-Kun; Wang, Jaw-Yuan (Translational Cancer Research, 2018)
Background: Deciding the most appropriate timing for surgical resection of locally advanced gastrointestinal stromal tumors (LAGISTs) has conventionally been challenging, because no well-established clinical guideline is available. In this study, we combined computed tomography (CT)-measured tumor density and Response Evaluation Criteria in Solid Tumors version 1.1 (RECIST 1.1) to evaluate the clinical responses in 12 patients with LAGISTs. We aimed to offer alternative approaches that can enhance the surgical resectability evaluation of LAGISTs after neoadjuvant therapy. Methods: This study recruited 12 consecutive patients diagnosed with LAGISTs who had received neoadjuvant imatinib therapy primarily at the study institution from December 2010 to December 2017. They were followed up until December 2017. Tumor responses were simultaneously analyzed by measuring tumor density on CT images and applying RECIST. Clinicopathological features, clinical outcomes, and KIT and PDGFR gene mutation profiles were also evaluated. Results: Analysis of tumor responses using the combined CT-measured tumor density and RECIST method revealed that 10 of 12 patients were considered as partial response (PR). One patient showed stable disease (SD) but was a borderline PR hence all 11 patients were resectable. Three of 7 GISTs patients who underwent resection were considered as stable disease according to RECIST but 2 of 3 were categorized as PR using our combined evaluation approach. The other one patient was a borderline PR with 28% of CT tumor density reduction. Of the 12 patients, five patients had KIT exon 11 deletion, two had KIT exon 11 insertion, three had point mutation and one was wild-type KIT and PDGFRA. However, KIT gene mutation status was not a useful indicator when evaluating surgical resectability in our study. Conclusions: We suggest that our combined CT-measured tumor density and RECIST evaluation method may be beneficial for deciding an appropriate timing for surgical resection of LAGISTs.